E-Visual English Instructions (EUIS) Through Figma to Improve English Primary School Teachers - Ishak, Ishak; Sumiyani, Sumiyani; Mulyanah, Euis Yanah (SCOPE: Journal of English Language Teaching, 2024)
Nowadays, technological support can be used to help teachers improve their listening skills through radio, audio cassettes, television, videos, computers, or internet media with various existing pages. Each type of technology provides opportunities for the teachers to explore their listening strategies through E-Visual English Instructions (EUIS) applications as a medium. The aim of the research is to find out the E-Visual English Instructions (EUIS) applications on smartphones can be useful for the primary school English teacher in Tangerang to increase their English skills, especially listening skills. This research used quantitative descriptive by the experimental pre-test posttest design consisted of 20 teachers, and the data was obtained after the researcher did the pretest, formative, evaluation, and post-test by collecting data through observations, tests, questionnaires, and documentation. The results of this study indicate that some teachers' use of the E-Visual English Instructions application can improve their understanding and interest in listening skills. Based on the average score of the teachers' formative tests and evaluation tests, The results show that the average score increased from 55.7 in the formative test under the direction of the researcher to 88.8 in the ability test without direction through the evaluation of the test. The analysis of the results means that there is improvement in teachers' listening skills and interest in using E-Visual English Instructions (EUIS) applications. Means that the use of this application is highly recommended in English language learning, especially in improving listening skills for elementary school English teachers.